The Poetic Version of Hes.Op.1-53 by Aquilino Iglesia Alvariño - Pereiro Pardo, Amelia (Madrygal. Revista de Estudios Gallegos, 2015)
In 1986 some unpublished translations of Aquilino Iglesia Alvariño were edited in view of the celebration of the “Día das Letras Galegas” in his honour. One of them was a Galician poetic version of the beginning of the poem Works and Days of Hesiod. The reading and translation of the Greek and Latin classics was one of the foundations of his poetry. Therefore, the aim of this work is to study this version of Hesiod and to learn more about his translations.